Environmentally conscious materials and chemicals processing (John Wiley & Sons, 2007)
The third volume of the Wiley series, Environmentally Conscious Material and Chemically Processing focuses on environmentally preferable approaches to designing and developing material and chemical processing. The book reflects the hierarchy of design, from tools for evaluating environmental hazards of industrial materials and chemicals through to the economics of environmental improvement projects. Major topics covered include: Chemical Manufacturing, Materials substitutions, Engineering processes, products, and systems to reduce environmental impacts, approaches for evaluating emissions and hazards of chemicals and processes, Environmental regulations, Properties and fates of environmental contaminants, and others.